The Role of Zakat in Alleviating Multidimensional Poverty - Pratama, Siectio Dicko (International Journal of Islamic Economics and Finance (IJIEF), 2023)
The potential of zakat is too huge to be ignored by the world. Recently, the notion to integrate zakat on the Sustainable Development Goals has grown rapidly. Nevertheless, the impact of zakat in Indonesia has not been pronounced and could doubt the adoption of zakat as a global tool. This paper aims to investigate the impact of zakat on monetary and multidimensional poverty by using the National Zakat Index developed by BAZNAS. Two components of the index that cover the environmental and impact of zakat are employed to sharpen the analysis. The main method used is multiple linear regression with control variables to identify the impact of zakat on multidimensional and monetary poverty. The analysis is also conducted to evaluate the performance and development of zakat in Indonesia. The result informed that the environment for zakat to grow in Indonesia still needs to be improved, particularly in Java. Meanwhile, the micro NZI that represents the performance of institution and impact of zakat on mustahik is the only variable that is significant to multidimensional poverty. Thus, it is recommended for the government to adopt a mandatory system of Zakat in the country as it can hasten the alleviation of poverty and achieving SDGs by 2030.